STUDY THE SPREAD OF WORMS EGGS IN REFRIGERATED CONTAINERS FOR SOFT DRINKS AND JUICES IN THE SUMMER IN THE PROVINCEOF DIWANIYAH - AL-CHAABAWI, SAFAA RESAN (Diyala Agricultural Sciences Journal, 2016)
This study was conducted to educate citizens to the unhealthy methodes in cooling the invasive drinks and juices in the summer and in the spread of refrigerated containers for thes fluids . The study showed after examining 120 refrigerated container in the province of Diwaniyah for duration three months are July,August and September that there obvious ratios existence. Eggs of parasites worms Faciola hepatica ,Faciola gigantica and Schistosoma hematobium. The total percentage parasite Faciola hepatica was 5% in the center of the province and the districts and counties the parasite Faciola gigantica 11.6% and the total percentage of the parasite Schistosoma hematobium was 5.5% . The containers has been divided to 60 in the center of the province and 60 in the province and district took three samples of water from each container for a number of samples 360 samples (180 of city center, 180 of the province and district), and then the ratios Seen eggs worm Faciola hepatica in the center is 6.6% either in districts, counties is 3.3%, while the worm Faciola gigantica, the percentages total to the presence of eggs in the samples is 11.1% in the city center either percentage Seen eggs in samples districts, counties are 12.2% was recorded eggs worm Schistosoma hematobium percentage amounted to 2.7% in the city center and 8. 3% in the districts and counties and the existence and spread of of these ratios leads to the spread of these worms and the spread of of parasitic diseases, so you should pay attention to the healthy ways to save invasive drinks, juices and healthy cooled and use ice cubes from water treatment.